Answers

2014-10-25T22:57:34+08:00
Let 'x' be Liza's age now
    'y' be Melanie's age now
    'z' be Lakan's age now
   'x-3' be Liza's age 3 years ago

x = 2 + y         ----equation 1
y = 3 + z         ----equation 2
x + y + z = 71  ----equation 3
from equation 2:
y = 3 + z
z = y - 3   ----equation 2'
substitute equations 1 and 2' to equation 3
x + y + z = 71
(2 + y) + y + (y - 3) = 71
3y = 71 + 3 - 2
3y = 72
y = 24
Liza's age now:
x = 2 + y
x = 2 + 24
x = 26 yrs old
Liza's age 3 years ago:
x - 3 = 26 - 3
       = 23 years old 
0
2014-10-26T10:02:24+08:00
3 years ago Liza was 23years old
0